Strategic Marketing Transformation in the Digital Age: Integrating AI, Big Data, and Sustainability for Competitive Advantage in Southeast Asia - Anthonius S Hutabarat; Irawan R D Budianto (DINASTI RESEARCH, 2026)
In the dynamic business environment of Indonesia and Southeast Asia (SEA), organizations must navigate rapid technological advancements, shifting consumer expectations, and intensifying global competition. The convergence of Artificial Intelligence (AI), Big Data analytics, and sustainability orientation offers unprecedented opportunities for strategic marketing transformation, yet empirical research integrating these dimensions remains limited in emerging market contexts. Drawing on Dynamic Capabilities Theory (Teece, 2016), the Technology Acceptance Model (Davis, 1989), and the Sustainable Marketing Framework (Belz & Peattie, 2012), this study develops and empirically tests a comprehensive model linking AI adoption, Big Data analytics capability, and sustainability orientation to marketing agility, innovation performance, and competitive advantage. Data were collected from 412 senior marketing executives in Indonesia, Malaysia, Singapore, Thailand, and Vietnam, representing the FMCG, retail, technology, hospitality, and manufacturing sectors. Using Structural Equation Modeling–Partial Least Squares (SEM-PLS), results indicate that AI adoption, Big Data analytics capability, and sustainability orientation each significantly enhance marketing agility and innovation performance, which in turn strongly predict competitive advantage (R² = 0.68). All seven hypotheses were supported, confirming the robustness of the model. The findings contribute theoretically by integrating technological and sustainability perspectives within a strategic marketing framework for emerging markets, and offer actionable insights for managers in SEA seeking to leverage digital transformation for sustained market leadership.